PERAN GURU DAN MEDIA PEMBELAJARAN DALAM MENSTIMULASI PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI - Nurtaniawati Nurtaniawati (Tunas Siliwangi, 2017)
Cognitive development is a strategic part in aspects of early childhood development, cognitive aspects in early childhood covers learning and problem solving, logical thinking and thinking symbolically. Based on the cognitive theory developed by Piaget and Vygotsky which states that children construct knowledge with direct experience with the social environment as scaffolding in this case be interpreted with the help of adults to children to achieve their development capabilities, particularly cognitive development. Help adults in the school environment are teachers than teachers of other things that help the process of child development is the media, where the media is a symbol of instruction for children in remembering obtain knowledge of early childhood are at Preoperational period. This paper discusses how the role of teachers and instructional media in stimulating cognitive development in early childhood, the importance of the role of teachers and the media in stimulating cognitive development in early childhood. The purpose of this article is the teacher know its role in stimulating children's cognitive development and can utilize existing media to stimulate cognitive development of children so that teachers have insight and knowledge with regard to cognitive development and how to stimulate them appropriately. Keywords: the role of teachers, instructional media, cognitive stimulation of children